The management agenda of the ninities capitals: the exemple of Recife and Salvador - Fernandes, Antônio Sérgio Araújo (Universidade Estadual Paulista / UNESP, 2007)
The paper discuss some the main policies of urbanization made in the ninety decade for Brazilian capitals local governments with social part icipat ion and public private paternship that agenda set of urban governance in Brazil. With focus in cases of Recife and Salvador, search it understanding the political aspects of differentiation of the same policies of urbanization in each one city.